PENGEMBANGAN MEDIA MADUPLINNG BERBASIS GOOGLE SITES PADA MATERI MAKHLUK HIDUP DAN LINGKUNGANNYA KELAS II SD - Zahra Aghniya, Hawa; Ismail, Ali; Ahmad Syahid, Aah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to determine the feasibility of using Google Sites-based Madupling media on living things and their environment in class II elementary school. Madupling media is a website-based learning media which contains material and quizzes. The method used in this research is the Research and Development (R&D) method by applying the ADDIE model (analyze, design, development, implementation and evaluation). Maduplimg media based on Google sites was validated by material and media experts by obtaining i-CVI and s-CVI values ​​of 1 indicating high suitability both in terms of material and media, so that this media was declared suitable for use. Then, this media was tested on 30 grade II elementary school students in Cibeureum II, Sumedang Regency, who gave a final SUS score of 91, indicating the excellent category or having a high level of usefulness. With this conclusion, Google Sites-based Madupling media has been proven to be valid and suitable for use in learning material about living things and their environment in class II elementary school.